Gestão do trabalho nos hospitais da 9ª região de saúde do Paraná - Mora, Cintia Teixeira Rossato (2015)
This study is characterized as a documentary and field research. It has as an objective to analyze the work management in hospitals of the 9th of Paraná Health Region, moreover, it tried to identify characteristics of the hospital network and health professionals in the technical and professional level. The first part of the research took place through the data collection in the National Health Facilities Register in April 2014, hospitals in the region were identified, as well as all health professionals who work in these units. Among the main results, in the 13 hospitals, 84.62% (11) were private and 61.54% (8) were small. It was identified 2,307 working occupations, from which 57.91% (1,336) were of higher education; 77.42% (1786) located in Foz do Iguaçu (health regional headquarters); 69.27% (1598) of the linkages work were classified as poor; 23.50% (376) had more than one occupation. Regarding the second step, the field research was carried out through semi-structured questionnaire filled out by the own researcher in meetings from November 2014 to February 2015, in the workplace of the subjects. It was interviewed 116 health professionals, from which 52.59% (61) were of a higher level and 47.41% (55) technical level, with specific training in health. The questions addressed socio-demographic aspects, training, work management (order of entry, type of relationship, career plans, jobs and salaries, program evaluation and other forms of performance assessment, progression and career promotion, payment bonuses and incentives) continuing education and political participation of the interviewed. Among the results it stood out: average age of 38.20 ± 14.73 years; female 72.41% (84); residents in Foz do Iguaçu 70.69% (82); belonging to the nurse staff 60.34% (70). The selection process was the primary form of entrance (56.43%), most of the bonds were protected, both in technical (95.84%) as the top-level (60.30%). The medical professional is the one with most unprotected bonds (100%), more than one job (84.61%) and higher salaries. Regarding the other aspects of the analyzed work management, it was identified in the professional responses the performance evaluation (25.71%), progression and career promotion (34.28%), bonus payments (13.57%) and incentive payments (29.29%). Lifelong learning occured sporadically in only 50% of cases, predominantly technical level (40%). As a conclusion it is noted that there is a hospital network of small institutions, from private nature, with a number of beds both general or complementary below recommended, divided workforce between doctors and nursing staff and lack of plan career, jobs and salaries in hospitals. It is recommended a greater regulation of the government in labor management in hospitals, regardless the ownership being public or private, since all are active in providing health services, which are considered by the Federal Constitution as a public relevance